Development and psychometric test of self-advocacy scale for patients with stroke - Zhixin Zhao; Jing Chen; Beilei Lin; Chunhui Zhang; Shanshan Wang; Yongxia Mei; Yunjing Qiu; Hu Jiang; Xiaoxuan Wang; Zhenxiang Zhang (Scientific Reports)
Abstract Self-advocacy is essential for self-management in stroke patients. However, a validated scale to assess the level of self-advocacy in this population is lacking. This study aimed to develop a self-advocacy scale for stroke patients and validate its psychometric properties. This cross-sectional study involved instrument development and psychometric testing, conducted in three stages. In stage 1, dimensions and items were generated through concept analysis, semi-structured interviews, and refined through a Delphi survey. Stage 2 focused on content and face validity assessment. Stage 3 evaluated psychometric properties. A total of 565 stroke patients participated in the items selection from August 2024 to November 2024. The self-advocacy scale was assessed through content validity, construct validity, internal consistency, and test-retest reliability. The study adhered to the STROBE checklist for reporting. From an initial 40-item pool, 24 items were retained after expert consultation and item analysis. The scale demonstrated a content validity index of 0.967. Exploratory factor analysis revealed a five-factor structure, explaining 68.285% of the total variance. Confirmatory factor analysis supported this structure with acceptable fit indices. The scale’s overall Cronbach’s α coefficient was 0.936, with the dimensions’ Cronbach’s α values ranging from 0.816 to 0.898. Split-half reliability was 0.874, and test-retest reliability was 0.885 (2-week interval). The 24-item self-advocacy scale for stroke patients demonstrated robust psychometric properties, providing a valid tool for clinical and research applications.